Pulse Rate of Jogging Two Kilometers of Constant Pace Running - Alfakqi, Muhammad Rifki; Yosika, Ghana Firsta; Suniga, John Paul C. (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The study aims to obtain data on the average pulse rate before and after running 5 laps to determine the level of dehydration of a person. The pulse is a form of the heart's ability, which is located in a certain area. The pulse rate can be used as a reference to determine heart rate, rhythm, and heart strength. The method used is to calculate the normal pulse rate, then the sample runs 5 laps of the soccer field, after the test the sample returns to calculate the pulse rate by holding the artery area and counting it for 1 minute while standing and calm. From the research conducted on a sample of 16 active PKO students, there are women and men, from the average data obtained, the results of the pulse rate is higher after running 5 laps, namely 168 times per minute, compared to before running 5 laps, with an average of 102 times per minute.